The impact of leadership traits and organizational learning on business innovation - Mai Ngoc Khuong; Thanh Tung Do; Nhu Ai Phan (Journal of Innovation & Knowledge (JIK), 2022)
The severe impact of the COVID-19 pandemic has forced many organizations to close or even shut down temporarily. In the literature, previous attempts have pointed to the role of leaders and learning in supporting firms to innovate and overcome such harsh and turbulent situations. This study investigates how different leadership personality traits affect business innovation both directly and indirectly through organizational learning. A total of 638 samples were collected from leaders working at tourism firms in Vietnam and analyzed using a quantitative approach and the partial least squares-SEM technique. The findings revealed that leadership personality traits, such as core self-evaluation, narcissism, the need for achievement, and risk propensity, have direct or indirect effects on business innovation. Moreover, knowledge acquisition, knowledge distribution, and knowledge interpretation are three organizational learning subprocesses that play mediating roles in the relationship between leadership traits and business innovation. Based on these findings, this study makes recommendations for tourism businesses to recover and develop sustainably following the pandemic.
Keywords: M00; M12; O32; Z32; 650; Organizational learning; Business innovation; Core self-evaluation; Narcissism; Need for achievement; Risk propensity